Optimalisasi Mengamankan Data Pribadi Menggunakan Kombinasi Algoritma ROT13 dan Caesar Chiper: Optimalisasi Mengamankan Data Pribadi Menggunakan Kombinasi Algoritma ROT13 dan Caesar Chiper - Harahap, Faisal Amir; Sovina, Mutiara; Lazuly, Ivi; Hanayah, Elen Tania (Publikasi Pengabdian Masyarakat, 2023)
In the era of the industrial revolution 4.0, the development of technological advancements is transforming increasingly sophisticated. The involvement of technology is felt from various aspects of activities and services that utilize information systems through the implementation of using a system. It becomes a threat that creates a crime that places a target on the security of personal data. So that provision and a strong foundation are needed to ensure the integration of data security and confidentiality in responding to threats of attacks and exploitation of information system security from irresponsible parties. Cryptography is a science that studies security techniques in information consisting of various algorithms such as ROT13 and Caesar Cipher. This study used the observation method through community service conducted at SMKN 13 Medan, literature study and mixed methods. The results of this study are able to provide an understanding regarding the security of students' personal data by optimizing the use of the ROT13 and Caesar Ciper algorithms. Through this research, it is hoped that it can become a source of reference on the importance of understanding personal data security so as to increase anticipation of information system security concerning personal data